Niche convergence suggests functionality of the nocturnal fovea - Moritz, Gillian L.; Melin, Amanda D.; Tuh Yit Yu, Fred; Bernard, Henry; Ong, Perry S.; Dominy, Nathaniel J. (Frontiers in Integrative Neuroscience, 2014)
The fovea is a declivity of the retinal surface associated with maximum visual acuity. Foveae are widespread across vertebrates, but among mammals they are restricted to haplorhine primates (tarsiers, monkeys, apes, and humans), which are primarily diurnal. Thus primates have long contributed to the prevailing view that the fovea is a functional adaptation to diurnal color vision. The foveae of nocturnal taxa, such as tarsiers, are widely interpreted as vestigial traits and therefore evidence of a diurnal ancestry. This enduring premise has been central to adaptive hypotheses on the origins of anthropoid primates; however, the question of whether the fovea of tarsiers is a functionless anachronism or a nocturnal adaptation remains open. To address this question, we focused on the diets of tarsiers (Tarsius) and scops owls (Otus), two taxa united by numerous anatomical homoplasies, including foveate vision. A functional interpretation of these homoplasies predicts dietary convergence and competition. This prediction can be tested with an analysis of carbon and nitrogen stable isotopes in tissues, which integrate dietary information. As predicted, the isotopic niches of Tarsius and Otus overlapped. In both Borneo and the Philippines, the δ13C values were indistinguishable, whereas the δ15N values of Otus were marginally higher than those of Tarsius. Our results indicate that both diets consisted mainly of ground-dwelling prey and raise the possibility of some resource partitioning. Taken together, our isotopic analysis supports a functional interpretation of the many homoplasies shared by tarsiers and scops owls, including a retinal fovea. We suggest that the fovea might function similarly in tarsiers and scops owls by calibrating the auditory localization pathway. The integration of auditory localization and visual fixation during prey detection and acquisition might be critical at low light levels.